Amorphous composite metal oxide hollow nano-microsphere material as well as preparation method and application thereof
By designing a spherical catalyst with a hollow structure, the internal cavity structure of the hollow nano microsphere material provides growth space for the nanocarbon material, solving the problem of catalyst inactivation due to the blockage of the pores of nanocarbon materials, and achieving high catalytic activity and high yield nanocarbon material synthesis.
Patent Information
- Application Number
- CN202411594825.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-10
AI Technical Summary
In the process of catalytic cracking of low-carbon hydrocarbons to synthesize nanocarbon materials, existing catalysts are prone to inactivation due to the blockage of pores by nanocarbon materials, resulting in isolation of reactants from the active center, which in turn limits the catalytic activity and the yield of nanocarbon materials.
A spherical catalyst with a hollow structure is designed, and the unique internal cavity structure of hollow nano microsphere materials is used to provide growth space for nanocarbon materials, increase the contact area between reactant molecules and catalysts, and reduce the transmission distance between reactant molecules to the active center.
The catalytic activity and yield of the synthesis of nanocarbon materials with catalytic cracking of low-carbon hydrocarbons is significantly improved, and the problem of nanocarbon materials blocking the catalyst channel is avoided, and the reaction efficiency is enhanced.
Smart Images

Figure CN119500129A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalytic materials, and relates to a hollow nano-microsphere material, a preparation method and use thereof, and in particular to an amorphous composite metal oxide hollow nano-microsphere material, a preparation method thereof and use thereof in catalytic cracking of low-carbon hydrocarbons to prepare nano-carbon materials. Background Art
[0002] Nanocarbon materials have been widely used in the field of new energy due to their good electrical and thermal conductivity. Catalytic cracking is the main method for preparing nanocarbon materials. In this method, the carbon source gas is decomposed into carbon atoms and hydrogen atoms under the action of a catalyst. The carbon atoms are deposited on the surface of the catalyst and self-assembled to form nanocarbon materials. In this method, the catalyst is the substrate for the growth of nanocarbon materials. The growing nanocarbon materials are prone to block the catalyst pores, blocking the contact between the active centers inside the catalyst particles and the reactants, causing the deactivation of the catalyst. Existing methods mainly improve this problem by adjusting the specific surface area and pore structure of the catalyst carrier, but the mesoporous channels of the catalyst particles provide limited growth space, and there are still many active centers inside the catalyst particles that cannot participate in the reaction.
[0003] Therefore, there is an urgent need to develop a more active catalyst that can improve the yield of nanocarbon materials while achieving the catalytic cracking of low-carbon hydrocarbons to synthesize nanocarbon materials. Summary of the invention
[0004] For the above problems, a spherical catalyst with a hollow structure can be designed to provide sufficient growth space for nanocarbon materials. The hollow nano-microsphere structure has the characteristics of unique internal cavity structure, low density, and high specific surface area, and has broad application potential in the field of catalysis. In the reaction of synthesizing nanocarbon materials by catalytic cracking, the shell layer of the hollow nano-microsphere structure has a good pore structure, which can ensure the entry of reactant molecules, and the unique internal cavity provides sufficient space for the growth of nanocarbon materials, avoiding the synthesized nanocarbon materials blocking the internal pores of the catalyst to cause the isolation of reactant molecules from the active center. In addition, the hollow nano-microsphere structure increases the contact area between the reactant molecules and the catalyst, reduces the transmission distance of the reactant molecules to the active center, and is conducive to improving the catalytic activity. Therefore, the present invention proposes an amorphous composite metal oxide hollow nano-microsphere material, and the prepared hollow nano-microsphere material exhibits high catalytic activity and nano-carbon material yield in the process of catalytic cracking of low-carbon hydrocarbons to synthesize nanocarbon materials.
[0005] The purpose of the present invention is to provide an amorphous composite metal oxide hollow nano-microsphere material and its preparation method and application in view of the deficiencies in the prior art, so as to improve the catalytic activity of catalytic cracking of low-carbon hydrocarbons to synthesize nano-carbon materials, thereby increasing the yield of nano-carbon materials.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides an amorphous composite metal oxide hollow nanometer microsphere material, which is a composite metal oxide of Fe2O3 and Al2O3, wherein the molar ratio of Al to Fe is (0.1-5):1, and has a hollow spherical structure, a diameter of the hollow sphere is 200-300nm, and a wall thickness is 20-40nm.
[0008] The present invention also provides a method for preparing the above-mentioned amorphous composite metal oxide hollow nano-microsphere material, which mainly comprises the following steps:
[0009] (1) dissolving a carbon source in deionized water to obtain a carbon source solution, subjecting the carbon source solution to a hydrothermal reaction, and then centrifuging, washing, and drying to obtain a carbon sphere template;
[0010] (2) a weak acid salt is dissolved in deionized water to obtain a weak acid salt solution, a corresponding weak acid is used to prepare a pH buffer solution, a carbon sphere template, an iron source and an aluminum source are added and stirred evenly, and ultrasonic crushing is performed until the mixture is uniformly mixed to obtain a mixed solution (preferably the ultrasonic crushing treatment is performed for 10 to 30 minutes);
[0011] (3) The mixed solution is heat-treated at 60-80° C. for 1-3 hours. After the heat-treatment, the mixed solution is centrifuged, washed, and dried to obtain a precursor. The precursor is calcined in air to obtain the amorphous composite metal oxide hollow nanospheres.
[0012] Furthermore, the carbon source is a combination of one or more of glucose, fructose, sucrose, maltose, starch, and citric acid, preferably glucose.
[0013] Furthermore, the concentration of the carbon source solution is 0.1 to 5 mol / L, preferably 0.3 to 1 mol / L.
[0014] Furthermore, the hydrothermal reaction is carried out in a sealed reactor, the hydrothermal reaction temperature is 170-190° C., the reaction time is 1-5 hours, preferably at 180° C. for 3-4 hours.
[0015] Furthermore, the centrifugation operation is carried out in a centrifuge, the centrifuge speed is 9000-11000 rpm, and the centrifugation time is 20-40 min.
[0016] Furthermore, in step (1) and step (3), deionized water and / or anhydrous ethanol are used for washing, and the number of washing times is 3 to 5 times.
[0017] Furthermore, the drying temperature is 70-90° C., and the drying time is 6-24 hours, preferably drying at 80° C. for 12 hours.
[0018] Furthermore, the weak acid salt is one or more of sodium citrate, sodium acetate, sodium oxalate, ammonium acetate, and ammonium formate, and the concentration of the weak acid salt solution is 0.1-1 mol / L (preferably 0.4 mol / L); the corresponding weak acid is one or more of citric acid, acetic acid, oxalic acid, and formic acid, and the pH of the pH buffer is 4.0-4.8.
[0019] Furthermore, the concentration of the weak acid salt solution is 0.1 to 1 mol / L.
[0020] Furthermore, the weak acid is one or more of citric acid, acetic acid, oxalic acid and formic acid.
[0021] Furthermore, the pH value of the pH buffer solution is 3 to 5, preferably 4.2 to 4.6.
[0022] Further, the iron source is one or more of ferric nitrate, ferric sulfate, ferric chloride, ferrous sulfate, and ferric acetate, and the concentration of the iron source in the mixed solution of step (2) is 0.1 to 100 mmol / L, preferably 4 to 10 mmol / L; and / or
[0023] The aluminum source is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, and alum, and the molar ratio of aluminum ions to iron ions in the mixed solution of step (2) is 0.1 to 5:1, preferably 2 to 3:1;
[0024] Furthermore, in the mixed solution of step (2), the concentration of the carbon sphere template is 0.1-5 g / L, preferably 0.8 g / L;
[0025] Furthermore, the precursor calcination process is carried out in a muffle furnace or a tube furnace, the calcination temperature of the precursor is 400-600° C., and the calcination time is 1-5 hours, preferably, after heating to 500° C. at a heating rate of 5° C. / min, calcining for 3 hours.
[0026] The present invention also provides the use of the amorphous composite metal oxide hollow nano-microsphere material in preparing nano-carbon materials by catalytic cracking of low-carbon hydrocarbons.
[0027] Furthermore, the specific operations of the application are:
[0028] (1-1) adding the above-mentioned amorphous composite metal oxide hollow nano-microsphere material into a fluidized bed reactor, and introducing gas to carry out a catalyst reduction process;
[0029] (2-2) After the reduction is completed, a reaction gas is introduced to carry out a synthesis reaction of the nanocarbon material, wherein the reaction gas is a mixture of a carbon source gas and an inert gas, and the volume ratio of the carbon source gas to the inert gas is 0.1 to 10:1 (preferably 1:1);
[0030] (3-3) After the reaction is completed, the nanocarbon material is collected, washed with alkali, acid, water and / or anhydrous ethanol, and dried to obtain a pure nanocarbon material.
[0031] Furthermore, the gas used in the reduction process is a mixture of hydrogen and an inert gas, the volume ratio of hydrogen to the inert gas is 0.1 to 2:1 (preferably 1:1), and the flow rate of the mixture during the reduction process is 20 to 40 cm 3 / s, the temperature of the reduction process is 600-800°C, the reduction time is 10-60min, and preferably the reduction is carried out at 750°C for 30min.
[0032] Furthermore, the inert gas is one of nitrogen, argon and helium.
[0033] Furthermore, the carbon source gas is one or more of methane, ethane, ethylene, propane, propylene, and butane.
[0034] Furthermore, the temperature of the synthesis reaction is 650-1000° C., and the reaction time is 40-180 min, preferably the reduction is carried out at 750° C. for 90 min.
[0035] Furthermore, the flow rate of the mixed gas in the synthesis reaction is 20 to 40 cm 3 / s.
[0036] Furthermore, the alkaline solution used in the alkaline washing process is sodium hydroxide or potassium hydroxide solution, the concentration of the alkaline solution is 0.5-3 mol / L, the alkaline washing temperature is 65-85°C, and the alkaline washing time is 4-24h. It is preferred to use 2 mol / L potassium hydroxide solution for alkaline washing at 80°C for 12h.
[0037] Furthermore, the acid used in the pickling process is one or more of hydrochloric acid, nitric acid, and sulfuric acid, the concentration of the acid solution is 0.5-3 mol / L, the pickling temperature is 65-85°C, and the pickling time is 4-24h. Preferably, 2 mol / L hydrochloric acid is used for pickling at 80°C for 12h.
[0038] Furthermore, deionized water and / or anhydrous ethanol are used for washing, and the number of washing times is 3 to 5 times.
[0039] Furthermore, the drying temperature in step (3-3) is 70-90°C, and the drying time is 6-24h, preferably drying at 80°C for 12h.
[0040] The nano-carbon material prepared in the above application process is formed by curling up several or dozens of carbon atomic layers, and has a hollow tubular structure with an outer diameter of 10 to 40 nm. The tube wall is composed of several or dozens of carbon atomic layers and a length of several microns.
[0041] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0042] (1) The amorphous composite metal oxide hollow nano-microsphere material prepared by the present invention has extremely high catalytic reaction activity and nano-carbon material yield in the process of catalytic cracking of low-carbon hydrocarbons to synthesize nano-carbon materials. The hollow nano-microsphere structure increases the contact area between the reactant molecules and the catalyst, reduces the transmission distance of the reactant molecules to the active center, and the unique internal cavity provides sufficient space for the growth of the nano-carbon material, avoiding the synthesized nano-carbon material blocking the internal pores of the catalyst and isolating the reactant molecules from the active center.
[0043] (2) The present invention controls the size of the carbon template by controlling the concentration of the carbon source solution and the time of the hydrothermal synthesis, thereby controlling the size of the internal cavity of the amorphous composite metal oxide hollow nano-microsphere material, and controls the shell thickness of the material by controlling the concentration of the iron source and the aluminum source in the solution. The present invention achieves the regulation of the catalytic performance of the material and the yield of the nano-carbon material by regulating the size of the internal cavity and the thickness of the shell of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is the SEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 1.
[0045] Figure 2 This is the TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 1.
[0046] Figure 3 This is the element distribution diagram of the amorphous metal oxide hollow nano-microsphere material prepared in Example 1.
[0047] Figure 4 This is the XRD spectrum of the amorphous metal oxide hollow nano-microsphere material prepared in Example 1.
[0048] Figure 5 This is the SEM image of the nanocarbon material synthesized in Example 1.
[0049] Figure 6 This is the TEM image of the nanocarbon material synthesized in Example 1.
[0050] Figure 7 This is the TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 2.
[0051] Figure 8 This is the TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 3.
[0052] Fig. 9 This is the TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 4.
[0053] Fig.10 This is the TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 5. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described in detail below with reference to specific embodiments.
[0055] Room temperature in the present invention refers to 25°C;
[0056] In the following examples, during the hydrothermal reaction, the volume of the glucose aqueous solution was 80% of the volume of the reactor; the pH of the pH buffer solution was 4.5-4.8.
[0057] The obtained nano-carbon material is formed by curling up several or dozens of carbon atomic layers, and has a hollow tubular structure in microscopic morphology, an outer diameter of 10 to 40 nm, a tube wall of several or dozens of carbon atomic layers, and a length of several microns.
[0058] All organic solvents used were purchased analytical grade unless otherwise specified.
[0059] Example 1: Synthesis of amorphous composite metal oxide hollow nano-microsphere material, comprising the following steps:
[0060] (1) A 0.6 mol / L glucose aqueous solution was placed in a reactor, the heating temperature was set to 180°C, and the hydrothermal reaction was carried out for 3.5 hours. After the reaction, the solution was naturally cooled to room temperature. The solution after the reaction was centrifuged and washed at a centrifuge speed of 1000 r / min for 30 minutes. The precipitate was washed alternately with deionized water and ethanol for a total of 4 times, and the precipitate was dried at 80°C for 12 hours to obtain a carbon sphere template.
[0061] (2) Dissolve 7.56g of ammonium formate in 300mL of deionized water, and add 1.02g of formic acid to prepare a pH buffer solution. Add 0.24g of carbon sphere template, 0.72g of aluminum sulfate and 0.43g of ferric nitrate to the above pH buffer solution and stir evenly. Ultrasonicate the mixed solution for 15min to evenly disperse the carbon spheres in the solution, keep it at 70°C for 2.5h and stir continuously. Centrifuge and wash after the insulation. The centrifuge speed is 1000r / min, the centrifugation time is 30min, and the precipitate is washed 3 times with deionized water. Dry the precipitate at 80°C for 12h to obtain a precursor. Place the precursor in a muffle furnace, heat to 500°C at a heating rate of 5°C / min, calcine for 3h and cool naturally to room temperature to obtain an amorphous composite metal oxide hollow nano-microsphere material with a bulk density of 450kg / m 3 , the specific surface area is 310m 2 / g.
[0062] Figure 1This is the SEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 1. Figure 2 This is a TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 1. Figure 1 , Figure 2 As shown, the diameter of the amorphous metal oxide hollow nano-microsphere material is about 180-200 nm, the inner diameter is about 150 nm, and the shell thickness is about 30 nm.
[0063] Figure 3 This is the element distribution diagram of the amorphous metal oxide hollow nanosphere material prepared in Example 1. Figure 3 As shown, the Fe and Al metal elements are evenly distributed in the hollow nano-microsphere material.
[0064] Figure 4 This is the XRD spectrum of the amorphous metal oxide hollow nanosphere material prepared in Example 1. Figure 4 As shown in the figure, the XRD spectrum of the material is a curve with a gently changing intensity, indicating that it is amorphous. From the perspective of the Scherrer formula, this curve can be regarded as the result of the extreme broadening and overlapping of the crystal diffraction peaks caused by the grain limit being too small, indicating that the metal oxide in the material exists in the form of microcrystals, showing a short-range ordered and long-range disordered structure, which promotes the uniform dispersion of the metal.
[0065] The steps of synthesizing nanocarbon materials using amorphous metal oxide hollow nano-microspheres as catalysts are as follows:
[0066] The amorphous metal oxide hollow nano-microsphere material is added to a fluidized bed reactor with a size of 40mm×1400mm and an addition amount of 1g. After the reactor is heated to 750℃ at a heating rate of 10℃ / min in a nitrogen atmosphere, 1L / min of hydrogen and 1L / min of nitrogen are introduced to reduce the catalyst for 30min. After the reduction is completed, 1L / min of ethane and 1L / min of nitrogen are introduced at 750℃ to synthesize the nanocarbon material for 90min. After the reaction is completed, it is naturally cooled to room temperature under nitrogen protection, the nanocarbon material is collected, and 2mol / L potassium hydroxide solution is used for alkaline washing at 80℃ for 12h, and then 2mol / L hydrochloric acid is used for acid washing at 80℃ for 12h. The nanocarbon material is filtered, and washed alternately with deionized water and ethanol for a total of 4 times, and dried at 80℃ for 12h to obtain pure nanocarbon material. The yield of nanocarbon material is 49.3g CNT / g cat (That is, the ratio of the mass of nanocarbon material to the mass of catalyst, the same below, no need to repeat it).
[0067] Figure 5 This is a SEM image of the nanocarbon material synthesized in Example 1. Figure 5As shown, the synthesized nanocarbon material is a fibrous structure with a large aspect ratio and an overall intertwined network structure. There is almost no trace of amorphous carbon particles and the purity is high.
[0068] Figure 6 TEM image of the nanocarbon material synthesized in Example 1. Figure 6 As shown, the synthesized nanocarbon material is a hollow tubular structure with an outer diameter of about 15 to 25 nm.
[0069] Example 2: Synthesis of amorphous composite metal oxide hollow nano-microsphere material, comprising the following steps:
[0070] (1) A 1.0 mol / L glucose aqueous solution was placed in a reactor, the heating temperature was set to 180°C, and the hydrothermal reaction was carried out for 4 hours. After the reaction, the solution was naturally cooled to room temperature. The solution after the reaction was centrifuged and washed at a centrifuge speed of 1000 r / min for 30 minutes. The precipitate was washed alternately with deionized water and ethanol for a total of 4 times. The precipitate was dried at 80°C for 12 hours to obtain a carbon sphere template.
[0071] (2) Dissolve 7.56g of ammonium formate in 300mL of deionized water, and add 1.02g of formic acid to prepare a pH buffer solution. Add 0.24g of carbon sphere template, 0.72g of aluminum sulfate and 0.43g of ferric nitrate to the above pH buffer solution and stir evenly. Ultrasonicate the mixed solution for 15min to evenly disperse the carbon spheres in the solution, keep it at 70°C for 2.5h and stir continuously. Centrifuge and wash after the insulation. The centrifuge speed is 1000r / min, the centrifugation time is 30min, and the precipitate is washed 3 times with deionized water. Dry the precipitate at 80°C for 12h to obtain a precursor. Place the precursor in a muffle furnace, heat to 500°C at a heating rate of 5°C / min, calcine for 3h, and naturally cool to room temperature to obtain an amorphous composite metal oxide hollow nano-microsphere material.
[0072] Figure 7 This is a TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 2. Figure 7 As shown, the diameter of the amorphous metal oxide hollow nano-microsphere material is about 300 nm, the inner diameter is about 270 nm, and the shell thickness is about 20 nm.
[0073] The steps of synthesizing nanocarbon materials using amorphous metal oxide hollow nano-microspheres as catalysts are as follows:
[0074] The amorphous metal oxide hollow nano-microsphere material is added to a fluidized bed reactor with a size of 40mm×1400mm and an addition amount of 1g. The reactor is heated to 750℃ at a heating rate of 10℃ / min in a nitrogen atmosphere, and 1L / min of hydrogen and 1L / min of nitrogen are introduced to reduce the catalyst for 30min. After the reduction is completed, 1L / min of ethane and 1L / min of nitrogen are introduced at 750℃ to synthesize the nanocarbon material for 90min. After the reaction is completed, it is naturally cooled to room temperature under nitrogen protection, the nanocarbon material is collected, and 2mol / L potassium hydroxide solution is used for alkaline washing at 80℃ for 12h, and then 2mol / L hydrochloric acid is used for acid washing at 80℃ for 12h. The nanocarbon material is filtered, and washed alternately with deionized water and ethanol for a total of 4 times, and dried at 80℃ for 12h to obtain pure nanocarbon material. The yield of nanocarbon material is 56.7g CNT / g cat .
[0075] Example 3: Synthesis of amorphous composite metal oxide hollow nano-microsphere material, comprising the following steps:
[0076] (1) A 0.3 mol / L glucose aqueous solution was placed in a reactor, the heating temperature was set to 180°C, and the hydrothermal reaction was carried out for 3 hours. After the reaction was completed, the solution was naturally cooled to room temperature. The solution after the reaction was centrifuged and washed at a centrifuge speed of 1000 r / min for 30 minutes. The precipitate was washed alternately with deionized water and ethanol for a total of 4 times. The precipitate was dried at 80°C for 12 hours to obtain a carbon sphere template.
[0077] (2) Dissolve 7.56g of ammonium formate in 300mL of deionized water, and add 1.02g of formic acid to prepare a pH buffer solution. Add 0.24g of carbon sphere template, 0.72g of aluminum sulfate and 0.43g of ferric nitrate to the above pH buffer solution and stir evenly. Ultrasonicate the mixed solution for 15min to evenly disperse the carbon spheres in the solution, keep it at 70°C for 2.5h and stir continuously. Centrifuge and wash after the insulation. The centrifuge speed is 1000r / min, the centrifugation time is 30min, and the precipitate is washed 3 times with deionized water. Dry the precipitate at 80°C for 12h to obtain a precursor. Place the precursor in a muffle furnace, heat to 500°C at a heating rate of 5°C / min, calcine for 3h, and naturally cool to room temperature to obtain an amorphous composite metal oxide hollow nano-microsphere material.
[0078] Figure 8 This is a TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 3. Figure 8 As shown, the diameter of the amorphous metal oxide hollow nano-microsphere material is about 200 nm, the inner diameter is about 120 nm, and the shell thickness is about 40 nm.
[0079] The steps of synthesizing nanocarbon materials using amorphous metal oxide hollow nano-microspheres as catalysts are as follows:
[0080] The amorphous metal oxide hollow nano-microsphere material is added to a fluidized bed reactor with a size of 40mm×1400mm and an addition amount of 1g. The reactor is heated to 750℃ at a heating rate of 10℃ / min in a nitrogen atmosphere, and 1L / min of hydrogen and 1L / min of nitrogen are introduced to reduce the catalyst for 30min. After the reduction is completed, 1L / min of ethane and 1L / min of nitrogen are introduced at 750℃ to synthesize the nanocarbon material for 90min. After the reaction is completed, it is naturally cooled to room temperature under nitrogen protection, the nanocarbon material is collected, and 2mol / L potassium hydroxide solution is used for alkaline washing at 80℃ for 12h, and then 2mol / L hydrochloric acid is used for acid washing at 80℃ for 12h. The nanocarbon material is filtered, and washed alternately with deionized water and ethanol for a total of 4 times, and dried at 80℃ for 12h to obtain pure nanocarbon material. The yield of nanocarbon material is 28.4g CNT / g cat .
[0081] Example 4: Synthesis of amorphous composite metal oxide hollow nano-microsphere material, comprising the following steps:
[0082] (1) A 0.6 mol / L glucose aqueous solution was placed in a reactor, the heating temperature was set to 180°C, and the hydrothermal reaction was carried out for 3.5 hours. After the reaction was completed, the solution was naturally cooled to room temperature. The solution after the reaction was centrifuged and washed at a centrifuge speed of 1000 r / min for 30 minutes. The precipitate was washed alternately with deionized water and ethanol for a total of 4 times. The precipitate was dried at 80°C for 12 hours to obtain a carbon sphere template.
[0083] (2) Dissolve 7.56g of ammonium formate in 300mL of deionized water, and add 1.02g of formic acid to prepare a pH buffer solution. Add 0.24g of carbon sphere template, 1.08g of aluminum sulfate and 0.65g of ferric nitrate to the above pH buffer solution and stir evenly. Ultrasonicate the mixed solution for 15min to evenly disperse the carbon spheres in the solution, keep it at 70°C for 2.5h and stir continuously. Centrifuge and wash after the insulation. The centrifuge speed is 1000r / min, the centrifugation time is 30min, and the precipitate is washed 3 times with deionized water. Dry the precipitate at 80°C for 12h to obtain a precursor. Place the precursor in a muffle furnace, heat to 500°C at a heating rate of 5°C / min, calcine for 3h and cool naturally to room temperature to obtain an amorphous composite metal oxide hollow nano-microsphere material.
[0084] Fig. 9This is a TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 4. Figure 4 As shown, the diameter of the amorphous metal oxide hollow nano-microsphere material is about 240 nm, the inner diameter is about 150 nm, and the shell thickness is about 40 nm.
[0085] The steps of synthesizing nanocarbon materials using amorphous metal oxide hollow nano-microspheres as catalysts are as follows:
[0086] The amorphous metal oxide hollow nano-microsphere material is added to a fluidized bed reactor with a size of 40mm×1400mm and an addition amount of 1g. The reactor is heated to 750℃ at a heating rate of 10℃ / min in a nitrogen atmosphere, and 1L / min of hydrogen and 1L / min of nitrogen are introduced to reduce the catalyst for 30min. After the reduction is completed, 1L / min of ethane and 1L / min of nitrogen are introduced at 750℃ to synthesize the nanocarbon material for 90min. After the reaction is completed, it is naturally cooled to room temperature under nitrogen protection, the nanocarbon material is collected, and 2mol / L potassium hydroxide solution is used for alkaline washing at 80℃ for 12h, and then 2mol / L hydrochloric acid is used for acid washing at 80℃ for 12h. The nanocarbon material is filtered, and washed alternately with deionized water and ethanol for a total of 4 times, and dried at 80℃ for 12h to obtain pure nanocarbon material. The yield of nanocarbon material is 33.5g CNT / g cat .
[0087] Example 5: Synthesis of amorphous composite metal oxide hollow nano-microsphere material, comprising the following steps:
[0088] (1) A 0.6 mol / L glucose aqueous solution was placed in a reactor, the heating temperature was set to 180°C, and the hydrothermal reaction was carried out for 3.5 hours. After the reaction was completed, the solution was naturally cooled to room temperature. The solution after the reaction was centrifuged and washed at a centrifuge speed of 1000 r / min for 30 minutes. The precipitate was washed alternately with deionized water and ethanol for a total of 4 times. The precipitate was dried at 80°C for 12 hours to obtain a carbon sphere template.
[0089] (2) Dissolve 7.56g of ammonium formate in 300mL of deionized water, and add 1.02g of formic acid to prepare a pH buffer solution. Add 0.24g of carbon sphere template, 0.54g of aluminum sulfate and 0.32g of ferric nitrate to the above pH buffer solution and stir evenly. Ultrasonicate the mixed solution for 15min to evenly disperse the carbon spheres in the solution, keep it at 70°C for 2.5h and stir continuously. Centrifuge and wash after the insulation. The centrifuge speed is 1000r / min, the centrifugation time is 30min, and the precipitate is washed 3 times with deionized water. Dry the precipitate at 80°C for 12h to obtain a precursor. Place the precursor in a muffle furnace, heat to 500°C at a heating rate of 5°C / min, calcine for 3h, and naturally cool to room temperature to obtain an amorphous composite metal oxide hollow nano-microsphere material.
[0090] Fig.10 This is a TEM image of the amorphous metal oxide hollow nanosphere material prepared in Example 5. Figure 5 As shown, the diameter of the amorphous metal oxide hollow nano-microsphere material is about 200 nm, the inner diameter is about 150 nm, and the shell thickness is about 20 nm.
[0091] The steps of synthesizing nanocarbon materials using amorphous metal oxide hollow nano-microspheres as catalysts are as follows:
[0092] The amorphous metal oxide hollow nano-microsphere material is added to a fluidized bed reactor with a size of 40mm×1400mm and an addition amount of 1g. The reactor is heated to 750℃ at a heating rate of 10℃ / min in a nitrogen atmosphere, and 1L / min of hydrogen and 1L / min of nitrogen are introduced to reduce the catalyst for 30min. After the reduction is completed, 1L / min of ethane and 1L / min of nitrogen are introduced at 750℃ to synthesize the nanocarbon material for 90min. After the reaction is completed, it is naturally cooled to room temperature under nitrogen protection, the nanocarbon material is collected, and 2mol / L potassium hydroxide solution is used for alkaline washing at 80℃ for 12h, and then 2mol / L hydrochloric acid is used for acid washing at 80℃ for 12h. The nanocarbon material is filtered, and washed alternately with deionized water and ethanol for a total of 4 times, and dried at 80℃ for 12h to obtain pure nanocarbon material. The yield of nanocarbon material is 44.9g CNT / g cat .
[0093] Through the experiment to investigate the effects of ventilation rate and reaction time on the reaction products during the synthesis reaction, the experiment of controlling a single variable found that when the ventilation rate increases or the reaction time is shortened, the color of the reaction product carbon nanomaterial becomes white, which is judged to be a shortened carbon nanomaterial, and the uniformity decreases. The reason is that the reaction is interrupted by the increase of gas velocity or the shortening of reaction time, and the growth of carbon nanomaterials is interrupted, and the reaction is incomplete. When the gas velocity decreases or the reaction time increases, the reaction product carbon nanomaterial is visible to the naked eye as flocculent, which is judged to be excessive cross-linking of carbon nanomaterials, and the uniformity is also reduced. The reason is that the reaction is excessive due to the decrease of gas velocity or the excessive reaction time, which causes excessive reaction, accumulation of carbon atoms on the catalyst surface, excessive cross-linking after growth bifurcation, so the optimal ventilation rate is determined to be 20-40cm 3 / s, the optimal synthesis reaction temperature is 650-1000℃, and the reaction time is 40-180min.
[0094] Comparative Example 1:
[0095] Dissolve 7.56g of ammonium formate in 300mL of deionized water, and add 1.02g of formic acid to prepare a pH buffer solution. Add 0.72g of aluminum sulfate and 0.43g of ferric nitrate to the above pH buffer solution and stir evenly. Keep the mixed solution at 70°C for 2.5h and stir continuously. Centrifuge and wash after the insulation. The centrifuge speed is 1000r / min, the centrifugation time is 30min, and the precipitate is washed 3 times with deionized water. Dry the precipitate at 80°C for 12h to obtain a precursor. Place the precursor in a muffle furnace, heat to 500°C at a heating rate of 5°C / min, and cool naturally to room temperature after calcination for 3h to obtain an amorphous composite metal oxide material.
[0096] The amorphous metal oxide material was added to a fluidized bed reactor with a size of 40mm×1400mm and an addition amount of 1g. The reactor was heated to 750℃ at a heating rate of 10℃ / min in a nitrogen atmosphere, and 1L / min of hydrogen and 1L / min of nitrogen were introduced to reduce the catalyst for 30min. After the reduction was completed, 1L / min of ethane and 1L / min of nitrogen were introduced at 750℃ to synthesize the nanocarbon material for 90min. After the reaction was completed, it was naturally cooled to room temperature under nitrogen protection, the nanocarbon material was collected, and 2mol / L potassium hydroxide solution was used for alkaline washing at 80℃ for 12h, and then 2mol / L hydrochloric acid was used for acid washing at 80℃ for 12h. The nanocarbon material was filtered, and washed alternately with deionized water and ethanol for a total of 4 times, and dried at 80℃ for 12h to obtain pure nanocarbon material. The yield of nanocarbon material is 14.5g CNT / g cat .
Claims
1. An amorphous composite metal oxide hollow nano-microsphere material, which is a composite metal oxide of Fe2O3 and Al2O3, wherein the molar ratio of Al to Fe is (0.1-5):1, and has a hollow spherical structure, a diameter of the hollow sphere is 200-300 nm, and a wall thickness is 20-40 nm.
2. A method for preparing the amorphous composite metal oxide hollow nano-microsphere material according to claim 1, comprising the following steps: (1) dissolving a carbon source in deionized water to obtain a carbon source solution, subjecting the carbon source solution to a hydrothermal reaction, and then centrifuging, washing, and drying to obtain a carbon sphere template; (2) a weak acid salt solution is obtained by dissolving a weak acid salt in deionized water, a corresponding weak acid is used to prepare a pH buffer solution, a carbon sphere template, an iron source and an aluminum source are added and stirred evenly, and ultrasonically crushed until the mixture is evenly mixed to obtain a mixed solution; (3) The mixed solution is heat-treated at 60-80° C. for 1-3 h. After the heat-treatment, the mixed solution is centrifuged, washed, and dried to obtain a precursor. The precursor is calcined in air to obtain the amorphous composite metal oxide hollow nanospheres.
3. The preparation method according to claim 2, characterized in that: The carbon source is one or more combinations of glucose, fructose, sucrose, maltose, starch and citric acid; and / or The concentration of the carbon source solution is 0.1-5 mol / L.
4. The preparation method according to claim 2, characterized in that: The hydrothermal reaction is carried out in a sealed reactor at a temperature of 170-190° C. for a reaction time of 1-5 h; and / or The centrifugation operation is carried out in a centrifuge, the centrifuge speed is 9000-11000 rpm, and the centrifugation time is 20-40 min; and / or The drying temperature is 70-90°C and the drying time is 6-24h.
5. The preparation method according to claim 2, characterized in that: The weak acid salt is one or more of sodium citrate, sodium acetate, sodium oxalate, ammonium acetate, and ammonium formate, and the concentration of the weak acid salt solution is 0.1-1 mol / L; the corresponding weak acid is one or more of citric acid, acetic acid, oxalic acid, and formic acid, and the pH of the pH buffer is controlled at 4.0-4.
8.
6. The preparation method according to claim 2, characterized in that: The iron source is one or more of ferric nitrate, ferric sulfate, ferric chloride, ferrous sulfate, and ferric acetate, and the concentration of the iron source in the mixed solution of step (2) is 0.1-100 mmol / L; and / or The aluminum source is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, and alum, and the molar ratio of iron ions to aluminum ions in the mixed solution of step (2) is 0.1-5:1; and / or In the mixed solution of step (2), the concentration of the carbon sphere template is 0.1-5 g / L.
7. The preparation method according to claim 2, characterized in that: The precursor calcination process is carried out in a muffle furnace or a tube furnace, the calcination temperature of the precursor is 400-600° C., and the calcination time is 1-5 h.
8. Use of the amorphous composite metal oxide hollow nano-microsphere material according to claim 1 or the amorphous composite metal oxide hollow nano-microsphere material obtained by the preparation method according to any one of claims 2 to 7 in the preparation of nano-carbon materials by catalytic cracking of light hydrocarbons.
9. The use according to claim 8, characterized in that: The specific operations of the application are: (1-1) adding the amorphous composite metal oxide hollow nano-microsphere material into a fluidized bed reactor and introducing gas to carry out a catalyst reduction process; (2-2) After the reduction is completed, a reaction gas is introduced to carry out a synthesis reaction of the nano-carbon material, wherein the reaction gas is a mixture of a carbon source gas and an inert gas, and the volume ratio of the carbon source gas to the inert gas is 0.1 to 10:1; (3-3) After the reaction is completed, the nanocarbon material is collected, washed with alkali, acid, water and / or anhydrous ethanol, and dried to obtain a pure nanocarbon material.
10. The use according to claim 9, characterized in that The gas used in the reduction process is a mixture of hydrogen and inert gas, the volume ratio of hydrogen to inert gas is 0.1-2:1, and the flow rate of the mixture in the reduction process is 20-40 cm 3 / s, the temperature of the reduction process is 600~800 ℃, and the reduction time is 10~60 min; and / or The inert gas is one of nitrogen, argon and helium; and / or The carbon source gas is one or more of methane, ethane, ethylene, propane, propylene, and butane; and / or The temperature of the synthesis reaction is 650-1000°C and the reaction time is 40-180 min; and / or The flow rate of the mixed gas in the synthesis reaction is 20~40 cm 3 / s; and / or The alkaline solution used in the alkaline washing process is sodium hydroxide or potassium hydroxide solution, the concentration of the alkaline solution is 0.5~3 mol / L, the alkaline washing temperature is 65~85℃, and the alkaline washing time is 4~24h; and / or The acid used in the pickling process is one or more of hydrochloric acid, nitric acid and sulfuric acid, the acid solution concentration is 0.5~3 mol / L, the pickling temperature is 65~85℃, and the pickling time is 4~24h; and / or The drying temperature in step (3-3) is 70-90°C, and the drying time is 6-24 hours.
Citation Information
Patent Citations
Method for preparing nano alumina hollow ball
CN101134586A
Preparation method and application of hollow multi-shell material containing amorphous components
CN114314651A
Amorphous carbon nanotube catalyst, preparation method and application
CN116764635A
Low-temperature preparation method of mixed reinforcement for in-situ growth of carbon nanotubes on surfaces of hollow microspheres
CN117187776A
Calcium oxide-based CO2 adsorbent with hollow microsphere structure and preparation method of calcium oxide-based CO2 adsorbent
CN117463283A